ANALISIS KLASIFIKASI KASUS TINDAK PIDANA PENCURIAN DENGAN POHON KEPUTUSAN MENGGUNAKAN ALGORITMA C4.5 (STUDI KASUS POLSEK TELANAIPURA): Crime, Decision Tree, Prediction, Profiling, Web, WEKA. - Puspitorini, Sukma; Simorangkir, Lucy; Dwi Larasati, Putri; Yanuar, Wendy; Yandri (LP2M Universitas Nurdin Hamzah, 2023)
Telanaipura Sector Police is the Republic of Indonesia's Police command structure at the sub-district level in Jambi Province. In the criminal investigation department, the telecommunication sector in processing criminal data is still done manually assisted with Microsoft Word so that the processing of the data has not been properly processed in order to carry out data analysis, evaluation and profiling of data on the increasing number and extent of crime. extensively. The aim of reducing crime rates is that it needs to be built web-based applications and tested using WEKA applications to help process and analyze data using data mining techniques using the decision tree method. In analyzing the data using the age, time, place of occurrence, crime decision tree as an attribute of the case and article theft as a class. In making this prediction application, the PHP and HTML programming languages ​​are used. And using databases using MYSQL and in analyzing using Microsoft Excel and WEKA. The data inputted is in the form of data on the offender, violation data and admin data. The attributes that are inputted in the WEKA application are attributes of age, time, place of occurrence, and crime and articles of violation as a class. The output generated from the WEKA application is in the form of rules or rules from the decision tree while the output generated by the web-based prediction interface results in article violation classes and generates reports on the perpetrator's actions, the number of crimes, crimes per period and per violation article. With the Mining Data Prediction Interface Criminal Classification on the Police of the Jambi Telecommunication Sector Using the Decision Tree Method Can Help the Telanaipura Jambi Sector Police in evaluating and profiling criminal offenders.